(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1987)
The site was excavated in advance of roadworks on the M90 motorway. Four phases of activity were recognized. Phase 1 A class 1 henge monument with a concentric ring of nine pits within. Beaker sherds were recovered from the ditch. A cremation lay outside the entrance. Phase 2 A small burial cairn with contiguous peristalith of stones surrounded by a ring of free standing monoliths. The monument of this phase was almost completely destroyed. Phase 3 A ring of eight free standing monoliths, graded in height from SW to NE; recumbent stones lay between the three tallest monoliths on the south-west arc. At the centre a possible ring cairn was accompanied by cremated burials in pits. Phase 4 The centre of the monument was used as a metallurgical workshop for smelting iron and casting leaded bronze.